2000
DOI: 10.1021/ol0060174
|View full text |Cite
|
Sign up to set email alerts
|

Staudinger Ligation:  A Peptide from a Thioester and Azide

Abstract: [reaction: see text] The technique of native chemical ligation enables the total chemical synthesis of proteins. This method is limited, however, by an absolute requirement for a cysteine residue at the ligation juncture. Here, this restriction is overcome with a new chemical ligation method in which a phosphinobenzenethiol is used to link a thioester and azide. The product is an amide with no residual atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
281
0
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 491 publications
(295 citation statements)
references
References 27 publications
2
281
0
9
Order By: Relevance
“…Generally, problems arising from heterogenic phase hydrogenation can be overcome by reducing the azido group of a pentofuranuronic building block with tertiary phosphines under well-established conditions of the Staudinger reaction (Staudinger and Meyer 1919;Staudinger and Hauser 1921;Leffler and Temple 1967;Gololobov et al 1981;Gololobov 1992;Simone et al 2005;Brase et al 2005;Van Rompaey et al 2005;Temelkoff et al 2006): a method introduced for azidosugars as early as 1964 (Messmer et al 1964). The applicability of the Staudinger reaction in peptide chemistry was confirmed in the early 2000s (Saxon et al 2000;Nilsson et al 2000), and its applicability to solid phase synthesis was shown in the same year (Malkinson et al 2000;Lundquist and Pelletier 2001). Staudinger ligation became a very useful technique in the field of bioconjugation methods (Schilling et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, problems arising from heterogenic phase hydrogenation can be overcome by reducing the azido group of a pentofuranuronic building block with tertiary phosphines under well-established conditions of the Staudinger reaction (Staudinger and Meyer 1919;Staudinger and Hauser 1921;Leffler and Temple 1967;Gololobov et al 1981;Gololobov 1992;Simone et al 2005;Brase et al 2005;Van Rompaey et al 2005;Temelkoff et al 2006): a method introduced for azidosugars as early as 1964 (Messmer et al 1964). The applicability of the Staudinger reaction in peptide chemistry was confirmed in the early 2000s (Saxon et al 2000;Nilsson et al 2000), and its applicability to solid phase synthesis was shown in the same year (Malkinson et al 2000;Lundquist and Pelletier 2001). Staudinger ligation became a very useful technique in the field of bioconjugation methods (Schilling et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The same homolytic nitro-carbon fragmentation can be diverted by capture of the carbon radical intermediate with oxygen gas (O 2 ) to deliver the amide oxygen from O 2 . This understanding was used to develop a straightforward protocol for the preparation of 18 O-labeled amides in peptides by simply performing the umpolung amide synthesis reaction under an atmosphere of 18 O 2 . P reparative needs in amide synthesis, particularly those in the peptide regime, continue to drive new methods for their construction (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The increasing success of peptide therapeutics, as well as continuing biophysical studies of peptides, have generally outpaced the scope of purely chemical methods for their preparation on scale (16,17).…”
mentioning
confidence: 99%
“…The absence of a metal catalyst (e.g., Cu) is important especially for in vitro and in vivo applications, because Cu is known to be cytotoxic [5]. Therefore, the traceless variant of the Staudinger ligation [6][7][8] independently developed by Raines et al [9] and Bertozzi et al [10] is employed for several applications in chemistry, biochemistry, and (radio)pharmacy. The connection of proteins [11,12], peptides, and peptide fragments [9,13], the glycosylation [14] of amino acids and peptides [15,16], the preparation of large-sized lactams [17,18], the functionalization of polymers [19], and the introduction of radiolabels [20][21][22][23] as well as fluorescence dyes [24][25][26] makes this reaction widely applicable.…”
Section: Introductionmentioning
confidence: 99%